An analysis of Okun's law for the Spanish provinces - Celia Melguizo (European Regional Science Association (ERSA), 2015)
The inverse relationship between unemployment and Gross Domestic Product (GDP), commonly known as Okun?s law, has been traditionally analysed in the economic literature. Its application to Spain is interesting as the strong impact of business cycles on unemployment is a particular feature of the Spanish economy. During the current economic downturn unemployment rate has more than tripled, accounting in 2013 for 26 percent of the working population. However, this phenomenon is not confined to recession periods. Before this economic crisis, the Spanish economy had experienced continuous growth, reducing unemployment rates from 20 percent of the labour force to levels slightly above the European average. The analysis of the relationship between unemployment and GDP for the Spanish case has been carried out at the national level and for the autonomous communities, but it has not been analysed for provinces, the territorial level closer to local labour markets. The aim of this paper is to analyse the provincial differences in the response of unemployment rates to GDP variations for the period spanning 1985 to 2011. In order to do so, we first test the time series properties of provincial GDP and unemployment. We carry out the Augmented Dickey Fuller and Philips Perrron traditional tests and tests that consider the presence of structural breaks. Then we estimate using the difference version of Okun?s law. The analysis is complemented with the use of VAR and PVAR techniques and the Impulse Response Functions (IRFs) associated to check the robustness of the results obtained from the difference specification in a framework that takes into account the endogeneity of GDP and unemployment. The data is taken out from the Spanish National Institute of Statistics (INE).The main results obtained in this study indicate that the provincial analysis matters. Our analysis provides more information than previous studies for Spain and the results justify resorting to a provincial approach, which is one of the main contributions of this paper. We find that provinces within regions show a different response in unemployment rate with respect to GDP variations, that is, autonomous communities are internally heterogeneous. Moreover, we obtain that provinces that suffer to a higher extent the economic shocks on unemployment are those where economic activity is concentrated and those located in the south.
Keywords: C32; C33; J23; R11; 330; Unemployment; Output fluctuations; Spanish provinces